A Comparison of Conventional Blocks and Stabilized Earth Blocks as Building Materials in Uganda - Nnadi, Ezekiel Ejiofor; Boniface, Nancy; Eze, Val Hyginus Udoka (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
In Uganda, the high cost of conventional cement and sand blocks has driven the widespread adoption of alternative building materials, such as wattle bricks, compressed earth blocks, and burnt bricks. Among these, compressed earth blocks have gained popularity due to their eco-friendly, energy-efficient, and biodegradable nature. Made by compressing damp soil at high pressure, these blocks offer an environmentally sustainable solution by minimizing deforestation and eliminating the need for firewood, which is often used in the production of traditional bricks. This study employed a case study methodology and utilized deliberate sampling to gather data, which was then analyzed using SPSS v20. The findings revealed that Stabilized Earth Materials (SEMs) have a stronger positive correlation with user satisfaction compared to conventional blocks, with a satisfaction rating of 0.651 for SEMs versus 0.602 for conventional blocks. Additionally, the study showed that SEMs had a notable impact on reducing construction costs, with a 4.8% cost difference in favor of SEMs. Based on these results, it is recommended that construction managers should consider increasing the use of stabilized earth materials. This shift could not only lead to significant cost reductions but also improve the overall quality of construction, making it a more sustainable and viable option for Uganda’s building industry.